Descriptive analysis of post-stroke patients in a neurological physical therapy unit - Paniagua-Monrobel, Mercedes; Escobio-Prieto, Isabel; Magni, Eleonora; Galan-Mercant, Alejandro; Lucena-Anton, David; Pinero-Pinto, Elena; Luque-Moreno, Carlos (Frontiers in Neurology, 2023)
Introduction Physical therapy (PT) is the mainstay treatment in functional recovery after suffering a stroke. It is important in the acute phase of hospitalization after a stroke and later in the ambulatory phase. Patients and methods The present study aimed to analyze the data provided by the clinical history (CH) of people with stroke (pwS) who received PT treatment in order to establish a “preferential patient profile” (PPP) that may benefit more from an early PT treatment. This was an observational, descriptive, and cross-sectional study. A total of 137 pwS who had been treated with PT were selected. Information provided age, gender, stroke type and localization, and start and end dates of the different PT treatments. A descriptive analysis of the variables was conducted using absolute frequencies and percentages for the qualitative variables. Student's t-test or the Mann–Whitney U-test was used to determine the relationship between the time and variables “stroke type,” “outpatient,” and “occupational therapy.” The Kruskal–Wallis H-test was applied for the “localization” variable. Results Of the entire sample, 57.7% were men, 65% had an ischemic stroke, and 48.9% had a stroke on the left side. The patients with hemorrhagic stroke had an increased number of hospital PT sessions (p = 0.01) and were younger (59.58 years) than patients with ischemic stroke (65.90 years) (p = 0.04). Discussion and conclusion Our results do not show significant differences between the persons < 65 years and the number of outpatient physiotherapy sessions performed, although the resulting values are close to significance. Our results suggest that the PPP is a young person, with a hemorrhagic and left or bilateral stroke.